The property sector approach to major projects risk, uncertainty and complexity. Issue 1 (3rd May 2020) - Perry, Keith
Abstract: This paper considers the approach that the UK property sector typically adopts when addressing a major project, primarily from the perspective of the key private sector players of developer and investor. With Infrastructure promoters now looking for real estate to contribute to funding - (i.e. land value capture) the paper gives key insights to the property approach that needs to be considered It describes how a successful major property project approaches issues such as sustainability, land assembly, planning, development impact, project management, construction, finance (including PPP models), letting of space, and forward sales. This paper was originally written before the 2008 Financial Crisis and the impacts of that context change on risk are in part still playing out, together now with the 2020 'Covid' Pandemic. Comments are therefore wherever possible made in an assumed 'stable market' context.